2017
DOI: 10.1002/aenm.201701966
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Processed Polymer/Nanocrystal Hybrid Solar Cells with Double‐Side Bulk Heterojunction

Abstract: derivatives of polythiophene, derivatives of fullerene, TiO 2 , CdSe, and CuInS 2 , etc., have been used for fabricating solar cells (SCs). [1][2][3][4][5][6][7][8][9][10][11] Aqueous-solution-processed polymer/nanocrystal (NC) hybrid solar cells (AHSCs) can effectively integrate the advantages of the polymer (e.g., flexibility and lightweight) and the inorganic NCs (e.g., high mobility and broad absorption), [12][13][14] and therefore be considered as an ideal system to further improve the performance of ASCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…[31,32] As shown in Figure 4d, the decay dynamics of ZnO:CdTe film are faster, which means better electron extraction efficiency compared with TiO 2 :CdTe films. [2,5,[7][8][9]13,15,17,[33][34][35][36][37][38][39][40] It is shown that the highest PCE (6.51%) and J sc (19.5 mA cm −2 ) have been obtained in this work. As a result, the probability of carrier recombination process becomes smaller.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…[31,32] As shown in Figure 4d, the decay dynamics of ZnO:CdTe film are faster, which means better electron extraction efficiency compared with TiO 2 :CdTe films. [2,5,[7][8][9]13,15,17,[33][34][35][36][37][38][39][40] It is shown that the highest PCE (6.51%) and J sc (19.5 mA cm −2 ) have been obtained in this work. As a result, the probability of carrier recombination process becomes smaller.…”
mentioning
confidence: 54%
“…This device presents a J sc of 19.5 mA cm −2 , V oc of 0.620 V, FF of 53.9%, and PCE of 6.51%. In our previous work, [17] it was confirmed that thicker photoactive layer improved the probability of the carrier recombination. As a comparison, the corresponding parameters of Device B are 18.8 mA cm −2 , 0.614 V, 50.8%, and 5.87%, respectively.…”
mentioning
confidence: 60%
See 3 more Smart Citations